Currarino syndrome with intramedullary spinal cord abscess related communication between the tethered cord and a presacral mass: A case report - Takahiro Jimbo; Kouji Masumoto; Yasuhisa Urita; Takato Sasaki; Kentaro Ono; Chikashi Gotoh; Toru Uesugi; Toko Shinkai; Hajime Takayasu (Elsevier, 2015)
We herein report the case of a 21-day-old boy in which the detection of an intramedullary spinal cord abscess led to the diagnosis of Currarino syndrome (CS). He had a complete phenotype of CS, including sacral agenesis, an anorectal malformation, a presacral mass, and spinal cord malformations. In addition, he had an intramedullary spinal cord abscess. Intramedullary spinal cord abscess is rare in CS and is thought to require immediate intervention. Therefore, we additionally reviewed the available literature and discussed the therapeutic approach for CS with an intramedullary cord abscess.